The structure of the yeast ribosomal RNA genes. I. The complete nucleotide sequence of the 18S ribosomal RNA gene from Saccharomyces cerevisiae. - Rubtsov, P M (1980)
The cloned 18 S ribosomal RNA gene from Saccharomyces cerevisiae have been sequenced, using the Maxam-Gilbert procedure. From this data the complete sequence of 1789 nucleotides of the 18 S RNA was deduced. Extensive homology with many eucaryotic as well as E. coli ribosomal small subunit rRNA (S-rRNA) has been observed in the 3'-end region of the rRNA molecule. Comparison of the yeast 18 S rRNA sequences with partial sequence data, available for rRNAs of the other eucaryotes provides strong evidence that a substantial portion of the 18 S RNA sequence has been conserved in evolution.